Multispectral photoacoustic microscopy of lipids using a pulsed supercontinuum laser - Buma, Takashi (Biomed Opt Express, 2017)
We demonstrate optical resolution photoacoustic microscopy (OR-PAM) of lipid-rich tissue between 1050–1714 nm using a pulsed supercontinuum laser based on a large-mode-area photonic crystal fiber. OR-PAM experiments of lipid-rich samples show the expected optical absorption peaks near 1210 and 1720 nm. These results show that pulsed supercontinuum lasers are promising for OR-PAM applications such as label-free histology of lipid-rich tissue and imaging small animal models of disease.